A detachable configuration for the precast beam-column connection using metallic damper as connector: Experimental investigation. (15th April 2023) - Wu, Congxiao; Zhu, Chunyuan; Li, Dingbin; Li, Changhong; Zhou, Yun; Lie, Wenchen; Wu, Congyong; Chen, Zhangyan
Abstract: A beam-column connection with satisfactory seismic performance and assembly efficiency is preferred in prefabricated structures. An evolved detachable configuration for the precast beam-column connection using metallic damper as connector (PCF-MDC-nuts) is proposed. The detachable connection significantly reduces the labor cost of building demolition, repair, and recycling. A specimen PCF-MDC-nuts was designed and constructed based on a precast "wet" connection (specimen PC)). A dog-bone damper was adopted in PCF-MDC-nuts as a sacrificial element. First, a laboratory test was performed on the damper, followed by the beam-column connection. The dominant failure pattern of the dog-bone damper, both in the damper and connection tests, was mainly out-of-plane flexural-torsional buckling. The test results show that PCF-MDC-nuts has a similar flexural strength as PC. The maximum in-elastic drift ratio of PCF-MDC-nuts has been improved to 5.48% compared to that of PC (3.27%). The degradation of PC-MDC-nuts was alleviated compared with PC. The cumulated absorbed energy and maximum equivalent viscous damping ratio of the PCF-MDC-nuts were 41.04 kN·m and 44.17%, respectively, while those of PC were 11.06 kN·m and 19.48%. The seismic performance of PCF-MDC-nuts was superior to PC. The concept of the proposed detachable configuration was justified. Highlights: A detachable configuration for the precast beam-column connection was proposed. The assembly efficiency and seismic performance of the novel connection is satisfactory. The detachable configuration is reliable and feasible. The energy-absorption capacity of the novel connection is improved.